Treatment of intracranial inflammatory myofibroblastic tumor with PD-L1 inhibitor and novel oncolytic adenovirus Ad-TD-nsIL12: a case report and literature review - Qian, Xiao; Ning, Weihai; Dunmall, Louisa Chard; Qu, Yanming; Wang, Yaohe; Zhang, Hongwei (Frontiers in Immunology, 2024)
Inflammatory myofibroblastic tumor (IMT) is a rare pathological entity, first described in 1939. This lesion is most common in the lungs, but there are also reports of involvement in other organs. The disease is currently diagnosed based on pathological results due to the lack of characteristic imaging changes. Surgical resection is currently an effective treatment for this disease, however, the disease is invasive and possesses the possibility of recurrence. Previous literature has reported a large amount of programmed death 1 (PD-1) expression in IMT tissues, which may suggest the effectiveness of immunotherapy for this disease. In this case report, we represent a case of a middle-aged male who received PD-1 inhibitor + oncolytic adenovirus, Ad-TD-nsIL12 treatment, after IMT resection surgery. This successful practice has given us a new direction for the treatment of IMT.